Postconflict countries: Strategy for rebuilding fiscal institutions - Sanjeev Gupta; Shamsuddin Tareq; Benedict Clements; Alex Segura-Ubiergo; Rina Bhattacharya (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2007)
This paper reviews the challenges and experiences in rebuilding fiscal institutions in postconflict environments, based on advice from the IMF's Fiscal Affairs Department to selected countries. The recommended strategy involved a three-step process of (i) creating a proper legal framework for fiscal management, (ii) establishing a central fiscal authority and a mechanism for co-ordinating foreign assistance, and (iii) designing appropriate tax policies while simultaneously creating simple tax administration and expenditure management arrangements. The advice was tailored to the circumstances of postconflict countries, and in some cases involved transitional measures that were not first best from an efficiency standpoint. In a similar vein, recommendations on revenue administration and expenditure management focused on the most basic tasks and procedures. In providing advice, care was taken to ensure that these measures were consistent with the eventual transformation to a modern fiscal management system.
Keywords: H30; K34; O43; 330; fiscal policy; tax; institutions; conflict